The Mechanics and Regulation of Variable Payout Annuities - Vittas, Dimitri (2012)
This paper discusses the mechanics and regulation of participating and unit-linked variable payout annuities. These annuities offer benefits that are not fixed in either nominal or real terms but depend on the performance of the fund or funds in which the underlying reserve assets are invested, their profit sharing features, and the treatment of longevity risk. The paper focuses on the treatment of investment and longevity risks by different types of these annuities and underscores the challenge of establishing a robust and effective framework of regulation and supervision for these products. The paper also addresses the exposure of annuitants to integrity risk and places special emphasis on the need for a high level of meaningful transparency.